2010
DOI: 10.1111/j.1478-3231.2010.02354.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of Wilson Disease: natural history, treatment, mutations analysis and phenotypic correlation

Abstract: Long-term follow-up shows a satisfactory response in the great majority of adequately treated patients with WD and survival coincides with that of the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 29 publications
1
118
1
6
Order By: Relevance
“…Medici V et al observed that penicillamine treated Wilson's diseases have higher liver iron or higher urinary prohepcidin compared to zinc treated patients (10) Bruha R et al observed that long term follow up of Wilson's diseases showed satisfactory response and survival comparable with general population. (32) In our study 45 out of 50 wilson's diseases children showed satisfactory response to panicillamine and zinc therapy and 5 (10%) patients died of fulminant Wilson's diseases. Ferenci P et al stresses importance on mutation analysis for family screening with a index case with known causative mutation.…”
Section: Discussionmentioning
confidence: 47%
“…Medici V et al observed that penicillamine treated Wilson's diseases have higher liver iron or higher urinary prohepcidin compared to zinc treated patients (10) Bruha R et al observed that long term follow up of Wilson's diseases showed satisfactory response and survival comparable with general population. (32) In our study 45 out of 50 wilson's diseases children showed satisfactory response to panicillamine and zinc therapy and 5 (10%) patients died of fulminant Wilson's diseases. Ferenci P et al stresses importance on mutation analysis for family screening with a index case with known causative mutation.…”
Section: Discussionmentioning
confidence: 47%
“…This can be achieved either by medical therapy or by liver transplantation, when the timeframe for a rescue with medical treatment is not wide enough [18,24,25]. With chelation treatment or liver transplantation, prolonged survival has become the norm [26,27].…”
Section: Treatmentmentioning
confidence: 97%
“…Zinc therapy (8,11,12), an alternative approach based on limiting gastrointestinal absorption of copper via induction of metallothioneins, small cytosolic proteins that sequester copper, has also been unsuccessful in patients with advanced WD. Liver transplantation for WD, which was first performed by T.E.…”
Section: O M M E N T a R Ymentioning
confidence: 99%
“…More advanced stages of WD, which involve severe liver disease or neurological presentations, have, however, been far more difficult to arrest with D-PA or other subsequently developed copper chelators, such as trientine (TETA) and tetrathiomolybdenate (TTM) (8)(9)(10)(11)(12). Zinc therapy (8,11,12), an alternative approach based on limiting gastrointestinal absorption of copper via induction of metallothioneins, small cytosolic proteins that sequester copper, has also been unsuccessful in patients with advanced WD.…”
Section: Wilson Disease: An Overabundance Of Coppermentioning
confidence: 99%